Water Rights - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The interviews in this pack explore a range of views on the meaning and value of the right to water. Some governments have included a right to water in their national constitution, but how meaningful is this?